(untitled) (Sebha University Conference Proceedings, 2024)
Because of the explosive growth in the volume of data and information limits the ability of companies to manage these data, information and control effectively, and with continuing high storage costs companies face makes data retrieval and preparation of copies problems, As well as the high prevalence of advanced information technologies almost daily impact on the efficiency and productivity of the business. This paper investigates the potential of using cloud computing in self-learning skill development for Libyan Modern High School students (third level, IT department). The research explores the concept of cloud computing and its characteristics in the context of e-learning. It then highlights the benefits offered by cloud computing, such as easy access to applications and resources, cost savings, and improved efficiency. However, the paper also acknowledges potential obstacles, including internet availability and security concerns. A field study was conducted with 30 students using Microsoft Live@Edu, a cloud-based e-learning platform. The study evaluated the program’s effectiveness in facilitating self-learning and assessed student perceptions of its importance, quality, and benefits. The analysis of the questionnaire results revealed that a majority of the students agreed on the program’s value and positive impact on their learning experience. They highlighted the benefits of easy access, anytime and anywhere availability, and features that support collaboration and communication. The paper concludes by suggesting that cloud computing holds promise for enhancing e-learning in Libyan high schools. However, it emphasizes the need to address internet connectivity limitations and security considerations for successful implementation.